Antigone - Žižek, Slavoj (Bloomsbury Academic, 2016)
"While it is common practice in contemporary theatre to re-contextualize a piece of work, the riskier--and Slavoj Zizek would argue more faithful--approach might be to change the actual story itself. Zizek's Antigone not only re-positions Antigone as a revolutionary political figure, it alters the narrative of the play itself. As Zizek puts it himself in the introduction to the play, 'Only one thing is sure: sticking to the traditional letter is the safest way to betray the spirit of the classic'. Philosophers have long been preoccupied with Antigone--Kierkegaard, Hegel, Plato and Judith Butler to name but a few--but never before has a philosopher had the audacity to throw fidelity to the wind and re-write one of the most classic plays in the history of theatre. This lack of fidelity is, of course, precisely the point: not only is this a fascinating new play in its own right, it is a political work calling into question our ideas of reverence to the canon, fidelity to the text and the notion of what 'faithfulness' might really mean. A brilliantly funny, moving and political play for those who are interested in reading and watching Antigone in a new way."--